(untitled) (Scientific journal of the Fergana State University, 2025)
This work presents the results of studying the structural and physical properties of two-component composites (1-x)PbFe₁₂O₁₉ – xPbTiO₃ obtained from pre-synthesized and mechanically activated powders. To control the physical properties of the composites, in addition to varying the dopant concentration from 0.2 to 0.8 in steps of 0.2, a mechanical activation (nanostructuring) method was employed. This method involves applying force to the powder using Bridgman anvils, as well as incorporating the shear deformation created by a rotating lower anvil. Using X-ray diffraction methods, a sharp decrease in the lattice parameters of the dopant at x = 0.4 in the initial composition and a similar sharp change in the hexagonal lattice parameters after mechanical activation were identified.